Social solidarity among Chinese Canadian evangelicals in short-term missions - Tam, J (2019)
This thesis examines how Chinese-Canadian evangelicals (CCEs) maintain social solidarity through short-term missions (STMs) to China. STMs are pilgrimage-like service trips that entails an individual to travel to a distant place to engage in social service for one or two weeks. This research draws on theoretical insights from Randall Collins’ interaction ritual chains (IRC) theory to examine the intersections of ethnicity, religion, and emotions at the macro-, meso-, micro-, and situational levels. This study involved over 131 in-depth interviews with 48 STM participants, observations of four STMs in 2015, and a two-year ethnography of a sending church north of the Greater Toronto Area in 2015-16. My first empirical chapter takes a macro-level perspective to investigating the global missions phenomenon. My findings reveal that the religious discourses that motivate the collective actions of transnational Chinese fundamentalist organizations are unstable, and this unity based on a religious pan-Chinese ethnicity is challenged by linguistic, geographic, generational, and ideological fractures. In my second chapter analyzing the meso-level CCE congregations, I observed how they maintained their organizational focus by operating cyclically and how each congregation’s members actively participated to maintain the pursuit of their mission. In my third chapter, I focus on the micro-level motivations for CCEs to engage in STM action. I connect contemporary neuroscience to IRC theory’s conception of IR “chains,” and suggested the concept be revised to “entangled chains.” I discuss how acknowledging the emotional entanglement of various identities should drive the analytical discussion of the self in modernity. My final chapter examines how situations of putative spiritual conflicts allowed STMers to generate various collective-effervescence outcomes. This thesis contributes to the sociology of religion and emotions and our understanding of communities by uncovering how social solidarity is generated and sustained at multiple levels of social organization.